Scientific-Research Activity of the Department of Transport Machines, Faculty of Mechanical Engineering –Technical University of Liberec at The Field of the Vehicles Engines - Stanislav Beroun; Ladislav Bartonicek; Josef Laurin; Lubomir Moc; Celestyn Scholz (Communications - Scientific letters of the University of Zilina, 2001)
The paper shows the technical solutions and the results of the research works, connected with the conversion of Diesel engines to spark ignition (SI) gas fuelled engines for the vehicles. The attention is paid to the comparision of the exhaust pollutions from the gas fuelled engines and from original diesel engines.